2020
DOI: 10.1039/d0cp04828c
|View full text |Cite
|
Sign up to set email alerts
|

Ion-specific interactions at calcite–brine interfaces: a nano-scale study of the surface charge development and preferential binding of polar hydrocarbons

Abstract: This research provides an atomic-level insight into the synergic contribution of mono- and divalent ions to interfacial characteristics of calcite surface exposed to electrolyte solution containing organic compounds. The emphasis...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…The RDF profiles given in Figure further confirm favoring carboxylate–sodium pairing near the calcite slab surface. Note that a special procedure ,, was adopted for calculating RDF profiles because of our atomic system not being spherically symmetric. To do so, RDF plots were obtained by counting and averaging pairs of particles within a semispherical cone space on the calcite surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RDF profiles given in Figure further confirm favoring carboxylate–sodium pairing near the calcite slab surface. Note that a special procedure ,, was adopted for calculating RDF profiles because of our atomic system not being spherically symmetric. To do so, RDF plots were obtained by counting and averaging pairs of particles within a semispherical cone space on the calcite surface.…”
Section: Resultsmentioning
confidence: 99%
“…Competitive affinity of different species (ions and dissolved organic compounds) for accumulating at an interface is of importance to many areas of surface science. , For instance, lab experiences have unanimously confirmed the ion-sensitive wettability response of carbonate rocks while treating at the same salinity level . In this regard, ion-engineered waterflooding has been applied as an effective technique for improving oil recovery from carbonate reservoirs. In this operation, an electrolyte solution with modified ionic composition is injected into a candidate petroleum reservoir to enhance oil recovery through shifting naturally oil-loving rocks to a more water-wet state . Wettability modification of carbonate reservoirs in that process is known to be driven by the so-called potential-determining ions (Ca 2+ , Mg 2+ , and SO 4 2– ), which tend to facilitate the release of surface-active compounds of crude oil, mostly composed of carboxylic acids, from the pore walls …”
Section: Introductionmentioning
confidence: 99%
“…To remove such uncertainties, atomistic simulation affords strong capability for examining the contribution of ions to the interfacial characteristics of minerals with sub-nanoscale resolution. Simulations have revealed that ions can either act as mediating agents to develop hydrocarbon-calcite interactions 41 , 46 – 48 or efficiently screen the attachment of hydrocarbons onto the surface 42 , 49 . While calcite turns into weakly water-wet state in the former condition, water-favoring character of the surface is advanced upon the screening by ions.…”
Section: Introductionmentioning
confidence: 99%
“…Then the calcite (1 0 4) surface was conducted the energy optimization and structure optimization, so as to obtain the stablest conformation, and fixed the calcite surface (1 0 4). The Ca atom and C atom were spatially constrained to avoid distortion or deformation of the slits walls, which was because of CaCO 3 thermodynamic and kinetic characteristics basis ( Badizad et al, 2020b ). 2) Build the corresponding supercell, and the vacuum layer thickness was 50 Å.…”
Section: Simulation Sectionmentioning
confidence: 99%